2012
DOI: 10.1097/inf.0b013e31826fd456
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cytokines and Chemokines During Febrile Episodes Associated With Endothelial Cell Damage and Plasma Leakage in Dengue Hemorrhagic Fever

Abstract: The alteration in the cytokine/chemokine kinetics during a febrile episode can be used as a predictor for severe dengue infection. The increased and decreased levels at different time points can indicate the disease progression related to vascular leakage in dengue hemorrhagic fever/dengue shock syndrome patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
99
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 26 publications
6
99
1
1
Order By: Relevance
“…The rest of studies reported no statistical difference or did not detect TNFa. By contrast, IL-10 stood out as the cytokine for which concentration was elevated in DHF relative to DF patients consistently in seven studies utilizing the WHO (1986)/WHO (1997) case definition (Table 3) (Brasier et al, 2012;Butthep et al, 2012;Chen et al, 2005;Green et al, 1999b;Houghton-Triviño et al, 2010;Nguyen et al, 2004;P erez et al, 2004). The association of dengue severity with circulating levels of IFNg was more heterogeneous (Table 4) (Bozza et al, 2008;Butthep et al, 2012;Chen et al, 2005;Nguyen et al, 2004;Soundravally et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…The rest of studies reported no statistical difference or did not detect TNFa. By contrast, IL-10 stood out as the cytokine for which concentration was elevated in DHF relative to DF patients consistently in seven studies utilizing the WHO (1986)/WHO (1997) case definition (Table 3) (Brasier et al, 2012;Butthep et al, 2012;Chen et al, 2005;Green et al, 1999b;Houghton-Triviño et al, 2010;Nguyen et al, 2004;P erez et al, 2004). The association of dengue severity with circulating levels of IFNg was more heterogeneous (Table 4) (Bozza et al, 2008;Butthep et al, 2012;Chen et al, 2005;Nguyen et al, 2004;Soundravally et al, 2014).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The association of dengue severity with circulating levels of IFNg was more heterogeneous (Table 4) (Bozza et al, 2008;Butthep et al, 2012;Chen et al, 2005;Nguyen et al, 2004;Soundravally et al, 2014). Three studies noted increased IFNg in DHF and/or DSS patients relative to DF patients or healthy controls (Bozza et al, 2008;Butthep et al, 2012;Nguyen et al, 2004), whereas three studies noted decreased IFNg levels in DHF/DSS over DF patients (Chen et al, 2005;Soundravally et al, 2014). Bozza et al (2008) noted defervescence phase IFNg levels in adults (age 15-73 years) were associated with disease severity (odds ratio=1.138, 95 %confidence interval1.041 to 1.245, P=0.0046).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations